DNA methylation-associated repression of MEST/PEG1 expression contributes to the invasion of extravillous trophoblast cells. (October 2016) - Peng, Wei; Chen, Ying; Luo, Xin; Shan, Nan; Lan, Xi; Olson, David; Zhang, Hua; Ding, Yu-Bin; Qi, Hong-Bo
Abstract: Introduction: The invasion of extravillous cytotrophoblasts (EVTs) into the maternal uterine decidua and vasculature is critical for human placenta development and pregnancy maintenance. The imprinted gene MEST/PEG1 has been implicated in trophoblast development; however, the role of MEST in EVT invasion and the accompanying early pregnancy complications are not fully understood. Methods: Western blot, immunofluorescence and immunohistochemistry were used to detect MEST protein expression and localization by using antibodies recognize 2 reported isoforms. Specific small interference RNA (siRNA) targeting both of the MEST isoforms was applied to silence MEST expression in extravillous explants and HTR8/SVneo cells. Cell invasion and migration were assessed using the Matrigel invasion, Transwell migration assay and the xCELLigence system. Promoter DNA methylation was examined using bisulfite-sequencing polymerase chain reaction (BSP). Results: MEST protein was highly expressed in EVTs in the first trimester placenta and in the invasive EVT cell lines HTR-8/Svneo and HPT-8. Weak MEST expression was found in cytotrophoblasts (CTBs) and the choriocarcinoma-derived CTB cell line JEG-3. The specific siRNA knockdown of MEST expression significantly reduced HTR-8/Svneo cell invasion and migration as well as extravillous explant outgrowth, which were associated with the downregulation of Twist, N-cadherin and Vimentin. Decreased MEST protein expression with isoform 2 promoter hypermethylation was observed in the placentas of missed abortions, suggesting a possible pathological mechanism of missed abortion. Conclusions: Suppressed expression of MEST was associated with its isoform 2 promoter hypermethylation ex vivo placenta tissues and in vitro cultured EVT cell line s . The present results provide a possible pathological mechanism of missed abortion. Highlights: MEST/PEG1 protein was highly expressed in the EVTs in the first trimester placenta. MEST/PEG1 reduces the trophoblasts invasion via inhibited Twist, N-cad passway. Loss of MEST/PEG1 gene expression was involved in the missed abortion.